Enhancing Tourism Marketing Performance Through Green Marketing Strategy and Consumer-based Brand Equity - Faerrosa, Lady; Pratama, Aryan Agus; Algifani, Muhammad Gaza (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
One crucial determinant of tourism performance is environmental sustainability. Unfortunately, not all tourist destinations have adopted environmentally friendly tourism practices, making it important to explore and research this issue. This study aims to analyze the impact of green marketing strategy and consumer-based brand equity (CBBE) on the sustainability of tourism marketing performance in Lombok Island. The research employed both qualitative and quantitative approaches. The researchers conducted interviews with 10 informants from among Lombok's tourism stakeholders and distributed questionnaires to 350 domestic tourists. Qualitative data was analyzed using content analysis, while quantitative was analyzed using multiple linear regression with the aid of SPSS. The results indicate that both green marketing strategy and CBBE have a positive and significant impact on tourism marketing performance. As this study utilizes a mixed-method approach, it provides a more comprehensive understanding of the key factors that can enhance tourism marketing performance. Consequently, these findings can serve as a basis for stakeholders in formulating policies for sustainable and environmentally friendly marketing concepts that align with the demands of their target consumers.